2013
DOI: 10.1111/prd.12029
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix mineralization in periodontal tissues: Noncollagenous matrix proteins, enzymes, and relationship to hypophosphatasia and X‐linked hypophosphatemia

Abstract: As broadly demonstrated for the formation of a functional skeleton, proper mineralization of periodontal alveolar bone and teeth – where calcium phosphate crystals are deposited and grow within an extracellular matrix – is essential to dental function. Mineralization defects in tooth dentin and cementum of the periodontium invariably lead to a weak (soft or brittle) dentition such that teeth become loose and prone to infection and are lost prematurely. Mineralization of the extremities of periodontal ligament … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 188 publications
2
50
0
2
Order By: Relevance
“…Interestingly, the genes most affected by Trps1 deficiency are those associated with MVs, cellular structures that initiate the mineralization process ( Table 2). In vivo, a combined deficiency of TNAP and PHOSPHO1 (Phospho1 Ϫ/Ϫ ; Alpl ϩ/Ϫ mice), two phosphatases that are significantly downregulated in Trps1-KD cells, resulted in a significant decrease of dentin mineralization and was sufficient to almost completely deplete MVs from the mantle dentin (49). Consistent with these data from animal models, loss of TNAP and PHOSPHO1 in Trps1-deficient odontoblastic cells is associated with a decreased number of MVs.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Interestingly, the genes most affected by Trps1 deficiency are those associated with MVs, cellular structures that initiate the mineralization process ( Table 2). In vivo, a combined deficiency of TNAP and PHOSPHO1 (Phospho1 Ϫ/Ϫ ; Alpl ϩ/Ϫ mice), two phosphatases that are significantly downregulated in Trps1-KD cells, resulted in a significant decrease of dentin mineralization and was sufficient to almost completely deplete MVs from the mantle dentin (49). Consistent with these data from animal models, loss of TNAP and PHOSPHO1 in Trps1-deficient odontoblastic cells is associated with a decreased number of MVs.…”
Section: Discussionsupporting
confidence: 63%
“…It has been demonstrated that expression of this gene is induced in odontoblasts prior to mineralization of the dentin (12,13,49). qRT-PCR and Western analyses show that Phospho1 is also significantly down-regulated in all Trps1-deficient odontoblastic cell lines in comparison with shScr control cells (Fig.…”
Section: Up-regulation Of Trps1 In Differentiated Odontoblastic Cellsmentioning
confidence: 82%
“…Pulp chamber expansion and thin dentin have been reported in some studies, while others declared no HPP effect on dentin formation. Enamel hypoplasia and severe tooth caries have also been reported in HPP patients (3,4).…”
Section: Oral Manifestations Of Hpp Include a Characteristicmentioning
confidence: 96%
“…These vesicles are released from the hypertrophic chondrocytes and mature osteoblasts, the cells responsible for endochondral and membranous ossification. Hypertrophic chondrocyte differentiation is related to high tissue nonspecific alkaline phosphatase (TNAP) activity and to the synthesis and secretion of type X and II collagens by proliferating and pre-hypertrophic chondrocytes (Golub 2009;McKee et al 2013).…”
Section: Mineralization Process and The Biogenesis Of Matrix Vesiclesmentioning
confidence: 99%